Hybrid plasmonic nanostructures based on controlled integration of MoS2 flakes on metallic nanoholes. Issue 36 (4th September 2018) - Garoli, Denis; Mosconi, Dario; Miele, Ermanno; Maccaferri, Nicolò; Ardini, Matteo; Giovannini, Giorgia; Dipalo, Michele; Agnoli, Stefano; De Angelis, Francesco
Abstract : A novel method for the preparation of hybrid 2D-material/plasmonic nanostructures paving the way toward hybrid plasmonic nanopores. Abstract : Here, we propose an easy and robust strategy for the versatile preparation of hybrid plasmonic nanopores by means of controlled deposition of single flakes of MoS2 directly on top of metallic holes. The device is realized on silicon nitride membranes and can be further refined by TEM or FIB milling to achieve the passing of molecules or nanometric particles through a pore. Importantly, we show that the plasmonic enhancement provided by the nanohole is strongly accumulated in the 2D nanopore, thus representing an ideal system for single-molecule sensing and sequencing in a flow-through configuration. Here, we also demonstrate that the prepared 2D material can be decorated with metallic nanoparticles that can couple their resonance with the nanopore resonance to further enhance the electromagnetic field confinement at the nanoscale level. This method can be applied to any gold nanopore with a high level of reproducibility and parallelization; hence, it can pave the way to the next generation of solid-state nanopores with plasmonic functionalities. Moreover, the controlled/ordered integration of 2D materials on plasmonic nanostructures opens a pathway towards new investigation of the following: enhanced light emission; strong coupling from plasmonic hybrid structures; hot electron generation; and sensors in general based on 2D materials.